2020
DOI: 10.1210/clinem/dgaa097
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure in Obese Women with Primary Hypothyroidism and Appropriate Levothyroxine Replacement Therapy

Abstract: Context Growing evidence suggests that appropriate levothyroxine (LT4) replacement therapy may not correct the full set of metabolic defects afflicting individuals with hypothyroidism. Objective To assess whether obese subjects with primary hypothyroidism are characterized by alterations of the resting energy expenditure (REE). Design Retrospective analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Another aspect to be considered is that hypothyroid treated patients could have metabolic differences with euthyroid subjects. Muraca et al have found that obese hypothyroid patients in LT4 therapy, with a normal serum TSH level when compared with euthyroid subjects, are characterized by reduced resting energy expenditure, which is in accordance with the hypothesis that THR may not completely correct metabolic disturbances due to hypothyroidism [53]. Mele et al [54] have found that compared with euthyroid obese patients, LT4 users presented higher adiposity.…”
Section: Discussionmentioning
confidence: 71%
“…Another aspect to be considered is that hypothyroid treated patients could have metabolic differences with euthyroid subjects. Muraca et al have found that obese hypothyroid patients in LT4 therapy, with a normal serum TSH level when compared with euthyroid subjects, are characterized by reduced resting energy expenditure, which is in accordance with the hypothesis that THR may not completely correct metabolic disturbances due to hypothyroidism [53]. Mele et al [54] have found that compared with euthyroid obese patients, LT4 users presented higher adiposity.…”
Section: Discussionmentioning
confidence: 71%
“…Indirect calorimetry was performed continuously, while lying quietly, after an overnight fast in a comfortable and thermoregulated room, for 30 minutes during the basal equilibration period with a ventilated hood system (Sensor Medics 2900; Metabolic Measurement Cart) in order to measure VO 2 and VCO 2 to calculate energy expenditure. The mean coefficient of variation (CV) values within the session for both O 2 and CO 2 measurements were below 2% 22 …”
Section: Methodsmentioning
confidence: 97%
“…Anthropometric features were assessed using a balance with stadiometer (SECA 711). Body composition was assessed as previously described 22 by BIA using a leg‐to‐leg TANITA SC‐240 MA Body Composition Analyzer (TANITA, Japan). Patients were asked to stand on the Body Composition Analyzer with bare feet and to remove all the accessories containing metal.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased thyroid function treated patients could be metabolically different when compared with normal subjects. Accordingly, it has been found that obese hypothyroid women on levothyroxine therapy, with normal circulating thyrotropin values, have a diminished energy expenditure, suggesting that standard levothyroxine replacement does not fully correct metabolic alterations related to hypothyroidism [ 101 ]. Furthermore, other studies have encountered that hypothyroid patients treated with levothyroxine showed higher adiposity and similar insulin resistance, but healthier lipid levels compared with euthyroid obese patients [ 102 ].…”
Section: Thyroid Hormone Treatment In Obese Patients With Hypothyroid...mentioning
confidence: 99%